2019
DOI: 10.1021/acsphotonics.9b01211
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsically 2D-Chiral Metamirror in Near-Infrared Region

Abstract: Many previously observed strong chiroptical effects are limited to chiral metamaterials with complex three-dimensional building blocks. Recently, chiral metamirrors consisting of planar elements are proposed to selectively reflect one particular circularly polarized light (CPL) while absorbing the other, with the reflected one either preserving or altering its spin state. However, they are limited by complicated subwavelength chiral profiles of their unit cells, which are challenging to fabricate in the visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…Maoz et al and Wang et al have reported respectively the enhanced CD in plasmonic nanohole arrays with the EOT effect [105,106], and the CD responses can also be tuned by adjusting the array period. It has been demonstrated a large differential transmission for LCP and RCP incidences in achiral nanoparticle arrays with the excitation of two different SLRs [107,108], and Cotrufo et al have shown that the surface lattice resonance in a handed planar rod array plays an important role in determining the spin-dependent emission of light [109]. Nevertheless, these structures are not truly chiral, and the CD responses are related to their extrinsic chirality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maoz et al and Wang et al have reported respectively the enhanced CD in plasmonic nanohole arrays with the EOT effect [105,106], and the CD responses can also be tuned by adjusting the array period. It has been demonstrated a large differential transmission for LCP and RCP incidences in achiral nanoparticle arrays with the excitation of two different SLRs [107,108], and Cotrufo et al have shown that the surface lattice resonance in a handed planar rod array plays an important role in determining the spin-dependent emission of light [109]. Nevertheless, these structures are not truly chiral, and the CD responses are related to their extrinsic chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these structures are not truly chiral, and the CD responses are related to their extrinsic chirality. Besides that, the excitation of the SLR modes in those structures requires to fulfill the index-matching conditions, the enhanced CD for the SRR arrays can only be observed under oblique incidences [107,108], and the CD magnitude for the nanohole arrays is still relatively weak [105,106].…”
Section: Introductionmentioning
confidence: 99%
“…2(d)] form a chiral triad, giving rise to the chiroptical effect. This mechanism of extrinsic chirality was first identified in nematic liquid crystals [52,53], and later in artificial planar structures [25,26,[54][55][56]. On the other hand, from the electrodynamic point of view, similarly to how it happens in conventional 3D-chiral media, the observed optical activity effect results from the simultaneous presence of electric and magnetic responses in the structure [57,58].…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, chiral metasurfaces have the potential to demonstrate multifunctional metalenses, such as multi-focal length metalenses. In addition, chiral metasurfaces can be applied to demonstrate chiral metamirrors [ 74 ], multi-mode orbital angular momentum (OAM) generators [ 65 ], OAM sensors [ 126 ], intense light sources [ 127 , 128 ], and color filters [ 129 ]. Apart from these applications, another significant application of chiroptical metasurfaces lies in chiral sensing [ 130 , 131 ], which can directly benefit biomedical and pharmaceutical industries.…”
Section: Discussionmentioning
confidence: 99%
“…Various natural systems such as molecules, DNA, and proteins possess chiral characteristics, and isomers of opposite handedness, called enantiomers, induce distinct optical chirality when they interact with circularly polarized light [ 70 , 71 ]. Examples of these chirality-related phenomena are CD [ 60 , 72 , 73 , 74 ], circular birefringence (CB) [ 75 , 76 , 77 ], the repulsive Casimir force [ 78 ], and the spin Hall effect [ 79 ].…”
Section: Fundamentals Of Chiroptical Metasurfacesmentioning
confidence: 99%